2020
DOI: 10.18231/j.ijogr.2020.101
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study to analyse the concordance in staging of carcinoma cervix between clinical examination, examination under anaesthesia and CECT

Abstract: Carcinoma cervix is the second most common gynaecological cancer among women in India, with high prevalence in rural regions. Accurate staging is imperative for providing appropriate treatment. This study aims to analyse the concordance among clinical examination, examination under anaesthesia, and CECT in evaluating the clinical components of the staging. Materials and Methods: Carcinoma cervix patients with clinical examination staging upto stage lll, admitted in government royapettah hospital, department of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…According to Hricak H et al, clinical staging has a sensitivity of 29 percent, CT has a sensitivity of 42 percent, and MRI has a sensitivity of 53 percent for detecting advanced stage (> or = IIB). When compared to surgical results, Ozsarlak et al found that the overall accuracy of staging for clinical examination, CT, and MRI was 47, 53, and 86 percent, respectively [12].…”
Section: Discussionmentioning
confidence: 99%
“…According to Hricak H et al, clinical staging has a sensitivity of 29 percent, CT has a sensitivity of 42 percent, and MRI has a sensitivity of 53 percent for detecting advanced stage (> or = IIB). When compared to surgical results, Ozsarlak et al found that the overall accuracy of staging for clinical examination, CT, and MRI was 47, 53, and 86 percent, respectively [12].…”
Section: Discussionmentioning
confidence: 99%